Resistance mechanisms - Cag, Yasemin; Caskurlu, Hulya; Fan, Yanyan; Cao, Bin; Vahaboglu, Haluk (Annals of Translational Medicine, 2016)
By definition, the terms sepsis and septic shock refer to a potentially fatal infectious state in which the early administration of an effective antibiotic is the most significant determinant of the outcome. Because of the global spread of resistant bacteria, the efficacy of antibiotics has been severely compromised. S. pneumonia, Escherichia coli (E. coli), Klebsiella, Acinetobacter, and Pseudomonas are the predominant pathogens of sepsis and septic shock. It is common for E. coli, Klebsiella, Acinetobacter and Pseudomonas to be resistant to multiple drugs. Multiple drug resistance is caused by the interplay of multiple resistance mechanisms those emerge via the acquisition of extraneous resistance determinants or spontaneous mutations. Extended-spectrum beta-lactamases (ESBLs), carbapenemases, aminoglycoside-modifying enzymes (AMEs) and quinolone resistance determinants are typically external and disseminate on mobile genetic elements, while porin-efflux mechanisms are activated by spontaneous modifications of inherited structures. Porin and efflux mechanisms are frequent companions of multiple drug resistance in Acinetobacter and P. aeruginosa, but only occasionally detected among E. coli and Klebsiella. Antibiotic resistance became a global health threat. This review examines the major resistance mechanisms of the leading microorganisms of sepsis.